Effect of Different Chelating Agents on the Bond Strength of Endodontic Sealers - Janani Karunakaran; Deepa Natesan Thangaraj; Kokila Sivakumar; Sebeena Mathew; Sinduja Rajamani (Indian Journal of Dental Sciences)
Aim: The aim of this study was to assess how the bond strength of AH Plus and MTA Bioseal is affected by 17% ethylenediaminetetraacetic acid (EDTA) and 0.2% chitosan. Methodology: Sixty single-rooted teeth all were sampled and decoronated to a length of 14 mm. ProTaper Gold had been employed for preparing canals up to the master apical rotary size F4. Between file modifications, the samples received irrigation with 5.25% sodium hypochlorite. Based on the chelating compounds used, the specimens (n = 20) were divided into three groups: 17% EDTA, 0.2% chitosan, and distilled water. The final rinse for samples had been neutral saline. The specimens (n = 10) were randomized to either of the two subgroups based on the sealer that was applied: Itena MTA Bioseal or AH Plus. Sections of each root’s coronal portion had been cut, each 2-mm thick. Crosshead speed of 1 mL/min had been utilized for the push-out bond strength test. Using a stereomicroscope, failure modes were quantitatively evaluated. Statistical Analysis: Two-way analysis of variance and Bonferroni’s post hoc test have been employed to statistically analyze bond strength data. Results: The coronal third of root samples had the strongest binding when MTA Bioseal containing 0.2% chitosan was used. Conclusion: With different root canal sealers, chitosan could be used as an alternate chelating agent. It improves the bonding of root canal sealers and has chelating properties as well.